2003
DOI: 10.1134/1.1618331
|View full text |Cite
|
Sign up to set email alerts
|

Exotic baryon states in topological soliton models

Abstract: The novel observation of an exotic strangeness S = +1 baryon state at 1.54 GeV will trigger an intensified search for this and other baryons with exotic quantum numbers. This state was predicted long ago in topological soliton models. We use this approach together with the new datum in order to investigate its implications for the baryon spectrum. In particular we estimate the positions of other pentaquark and septuquark states with exotic and with non-exotic quantum numbers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

33
169
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(203 citation statements)
references
References 13 publications
33
169
1
Order By: Relevance
“…[15] (fits A and B in Figure 4) with our results from Table II, we have found that our case (iii) with 4.3 ≤ e ≤ 4.7 supports fit B, and for 4.4 ≤ e ≤ 4.6 agrees nicely with fit A. Both fits A and B from [15] lie between 4.0 ≤ e ≤ 4.6 for case (ii). Case (iii) with 4.2 ≤ e ≤ 4.7 also supports the results presented in Table 1.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…[15] (fits A and B in Figure 4) with our results from Table II, we have found that our case (iii) with 4.3 ≤ e ≤ 4.7 supports fit B, and for 4.4 ≤ e ≤ 4.6 agrees nicely with fit A. Both fits A and B from [15] lie between 4.0 ≤ e ≤ 4.6 for case (ii). Case (iii) with 4.2 ≤ e ≤ 4.7 also supports the results presented in Table 1.…”
supporting
confidence: 75%
“…We hope that the present calculation, taken together with the analogous calculation in [7,13,15,16,26,27,28,29] will contribute to the understanding of the overall picture of the baryonic mass spectrum and mass splittings in the Skyrme model, as well as to further computations of other nonperturbative, dimension-6 operator matrix elements between different baryon states [43,44].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exotic multiquarks are expected since the early works of Jaffe [5,6], and some years ago Diakonov, Petrov and Polyakov [7] applied skyrmions to a precise prediction of Θ + . Very recent studies suggest that Θ + is a pentaquark state [8]. The nature of this particle, its isospin, parity [9] and angular momentum, are yet to be determined.…”
mentioning
confidence: 99%
“…Some features of exotic baryon spectra obtained previously within topological soliton model [26,7,27,28,29] can be understood in the framework of pentaquark model, independently of its particular variant (see, e.g. [30]).…”
mentioning
confidence: 99%